Involvement of ACSM family genes in the reprogramming of lipid metabolism within tumors and their investigation as promising therapeutic targets - Fang, Ke-Xin; Li, Zi-Qi; Dong, Jin-Liang; Yu, Ze (Frontiers in Cell and Developmental Biology, 2025)
Metabolic reprogramming of tumor cells is an important feature of oncogenesis and progression, with lipid metabolism playing a key role in this process. The enzymes encoded by the ACSM (Acyl-CoA Synthetase Medium-Chain Family) genes play a crucial role in fatty acid activation, affecting the energy supply and membrane synthesis of tumor cells. In recent years, research on the expression patterns of ACSM family genes in different tumor types and their regulatory mechanisms has gradually increased, revealing their close relationship with tumor development. However, current research on ACSM family genes still has some shortcomings, such as a lack of systematic large-scale clinical data support and an in-depth understanding of their regulatory networks. This work summarizes the role of ACSMs in tumor lipid metabolic reprogramming and explores their research progress as potential therapeutic targets, providing new ideas for future tumor treatment.